2021
DOI: 10.4103/jisp.jisp_287_20
|View full text |Cite
|
Sign up to set email alerts
|

Oral health of individuals with dementia and Alzheimer's disease: A review

Abstract: This paper explores the epidemiological evidence about oral health of individuals with neurodegenerative conditions of Alzheimer's disease (AD) and dementia. PubMed, Web of Science, and Scopus were searched to identify the relevant research papers published during January 2012 to June 2020. All cross-sectional, case–control, and cohort studies reporting oral and dental morbid conditions for status and association with AD and dementia were explored. The explored literature from 22 studies shows that oral health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…Estudos tem sugerido uma associação entre distúrbios neurológicos e a disfunção salivar, assim como as medicações utilizadas no tratamento da doença de Alzheimer causam a xerostomia como efeito colateral (DELWEL, et al, 2018;HAMZA, et al, 2021). Gao et al (2020) reporta que pacientes com doença de Alzheimer apresentam uma redução no fluxo salivar, mais especificamente da glândula submandibular, tanto quando estimulados tanto quando em repouso.…”
Section: Resultsunclassified
“…Estudos tem sugerido uma associação entre distúrbios neurológicos e a disfunção salivar, assim como as medicações utilizadas no tratamento da doença de Alzheimer causam a xerostomia como efeito colateral (DELWEL, et al, 2018;HAMZA, et al, 2021). Gao et al (2020) reporta que pacientes com doença de Alzheimer apresentam uma redução no fluxo salivar, mais especificamente da glândula submandibular, tanto quando estimulados tanto quando em repouso.…”
Section: Resultsunclassified
“…The residents in LTCF often have impaired cognition, and dementia is common. In previous studies, edentulism was associated with low cognition, and Alzheimer’s disease was linked to higher oral bacterial load and inflammation levels [ 51 ]. Alzheimer’s disease increases the risk for tooth loss, as oral cleaning is neglected or even forgotten when functional capacity is impaired.…”
Section: Discussionmentioning
confidence: 99%
“…A well-established association exists between poor oral health, specifically periodontitis, and an increased risk of developing AD or PD (Fig. 3 ) [ 100 102 ]. A cross-sectional study has revealed links between oral health-related stressors and neuropsychiatric symptoms in patients with AD [ 103 ].…”
Section: Oral Microbiotamentioning
confidence: 99%